(untitled) (مجلة جامعة بابل للعلوم الانسانية, 2017)
Abstract The research is characterized by the aesthetics of the grotesque in the art of painting and sculpture of the European Renaissance in the presentation of the nature of the influence of the aesthetics of the grotesque on the arts of the European Renaissance. The research included four chapters: The first chapter deals with the methodological framework of the research represented by the research aims to identify the aesthetics of the grotesque In the art of painting and sculpture of the European Renaissance). The limits of the research were limited to the study of the aesthetics of the grotesque art of painting and sculpture of the European Renaissance and the analysis of photographic models from the year 1400-1700. The second chapter consisted of two topics. The first topic dealt with the concept of Grouts, while the second topic dealt with the aesthetics of Grotesk in the arts of the European Renaissance. The second chapter ended with a set of indicators. While the third chapter deals with the applications of the aesthetics of the grotesque in the arts of the European Renaissance through the research procedures that contained the research community and its model, the research methodology, and the analysis of a set of models (5) model. The fourth chapter included the results of the research, its conclusions, as well as the recommendations and proposals. The researchers reached a number of conclusions and conclusions, including: 1 - The artist in the Western plastic arts to portray distorted shapes or some of the bodies in a disgusting and exaggerated in detail to achieve cynicism and the aesthetic and semantic effect it seeks. 2 - The concept of Grotesk was linked to the form and content of the Western plastic arts with the themes of ancient myths through the embodiment of the superstitious forms that are different from the familiar and characterized by greatness (the giant). employed Grotesk in the religious architecture became forms of the concept of Grotesk in Western plastic art as a way to remind and entice those who are outside the cathedral and attracted to this holy place through the content of the themes embodied by the forms of the grotesque.